Wayfinding for pedestrians: overview of the role of sidewalk design - Lesmana, Widi; Retna Hidayah; Triyono, Mochamad Bruri; Minghat, Asnul Dahar; Mustakim, Siti Salina (Science Publishing Corporation, 2018)
The primary aim of this study was to describe the pattern of pedestrian movement and the main cause of students’ selection in choos-ing those particular route. A qualitative research method was utilized for the purpose of data collection via an interview data retrieval technique. Findings were transcribed, coded, and analyzed manually. Findings indicated that students’difficulties in finding Rec-torate Building were27.5%. There were 75% of students who receive information for directions from the results of questioning with other students in the campus, while those who only read the guidemapwere only 25%. There were 55% of students choose route based on the closest distance, while comfort factor is 11.25%. Only 71.25% students use sidewalks, while those who do not always use pavements were 28.75%. Viewed from gender, it was indicated that difficulties in finding Rectorate Building was44.7% from male and 38.1% from female. 60.5% of male and 73.8% of female prefer to ask verbally to find travel information, while 39.5% of male and 26.2% of female would read the guide map. 59.5% female and 31.5% of male prefer the shortest route. The users of side-walks were 52.6% male and 69.2% female. This study contributes to the implementation and integration of sustainable green campus in Indonesia.